2008
DOI: 10.1128/aem.02528-07
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Supplementation of Caprylic Acid in Feed Reduces Campylobacter jejuni Colonization in Broiler Chicks

Abstract: Poultry colonized with Campylobacter species are a significant source of human food-borne illness. The therapeutic use of the medium chain fatty acid caprylic acid consistently reduced enteric C. jejuni colonization in chicks by 3 to 4 logs in three separate trials. These results support caprylic acid's potential to reduce Campylobacter carriage in poultry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Similarly, other studies conducted with day old chicks fed diets with different doses of caprylic acid alone have demonstrated significantly higher bacterial clearance in the ceca of birds that received a 0.7% or higher concentration of the fatty acid for last 3 or 7 days of the infection period [64,65,66]. However, two studies have shown that adding different doses of caprylic acid to drinking water or adding capric, caprylic or caproic acids to the feed for 3 days did not change the cecal colonization 11 days post infection in 70 or 27 day old broilers suggesting that the water soluble caprylic acid was absorbed in the intestine and did not reach ceca at levels adequate to clear the bacteria [67,68]. Among other SCFAs, butyrate has been shown to have antibacterial activity against Campylobacter in culture but it had no effect on cecal colonization when it was added to the broiler feed for two weeks prior to the oral challenge with C. jejuni [69,70].…”
Section: Effect Of Fatty Acids On Salmonella and Campylobacter Invmentioning
confidence: 99%
“…Similarly, other studies conducted with day old chicks fed diets with different doses of caprylic acid alone have demonstrated significantly higher bacterial clearance in the ceca of birds that received a 0.7% or higher concentration of the fatty acid for last 3 or 7 days of the infection period [64,65,66]. However, two studies have shown that adding different doses of caprylic acid to drinking water or adding capric, caprylic or caproic acids to the feed for 3 days did not change the cecal colonization 11 days post infection in 70 or 27 day old broilers suggesting that the water soluble caprylic acid was absorbed in the intestine and did not reach ceca at levels adequate to clear the bacteria [67,68]. Among other SCFAs, butyrate has been shown to have antibacterial activity against Campylobacter in culture but it had no effect on cecal colonization when it was added to the broiler feed for two weeks prior to the oral challenge with C. jejuni [69,70].…”
Section: Effect Of Fatty Acids On Salmonella and Campylobacter Invmentioning
confidence: 99%
“…Previous research conducted by our laboratory 15,20,30 and others [31][32][33] have highlighted the variability between trials when evaluating pre-harvest treatments against enteric Campylobacter. Because of this inherent variability associated with Campylobacter colonization studies, results from a single pre-harvest study may not fully evaluate the consistency or effectiveness of a Campylobacter intervention strategy.…”
Section: Advances In Food Technology and Nutritional Sciencesmentioning
confidence: 99%
“…Young chickens were used in this study because previous results from our laboratory demonstrated that young birds can be used as a reliable model to study Campylobacter colonization in market age birds. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…In a study that involved day-old chicks supplemented with caprylic acid in feed, Solis de los Santos et al (2008b) reported that 0.7% caprylic acid reduced C. jejuni colonization. Further, the therapeutic potential of caprylic acid for reducing C. jejuni was also explored with supplementation of caprylic acid to 15-d-old chicks 72 h before necropsy.…”
Section: Caprylic Acid On Salmonella Enteritidis and C Jejunimentioning
confidence: 99%